IMPLIKASI GEOSTRATEGIS KERJASAMA PERTAHANAN INDONESIA-TURKI TERHADAP POSISI INDONESIA DI ASIA TENGGARA : Studi Kasus Pembuatan Kaplan Medium Tank Periode 2014-2020 - Aditya Eka Sasmita (2022)
This study was conducted to provide an analysis of the implications of Indonesia-Tuki military cooperation on Indonesia's position in Southeast Asia. The author narrows it down in cooperation to make Kaplan Medium Tank. This thesis research also uses the concept of geopolitics, geostrategy in terms of defense interests and economic interests, defense cooperation theory and regional power theory, plus the use of qualitative methods (case studies) with explorative research types in the analysis process. In this study, it was found that according to a geostrategic perspective or national security, Indonesia's position is very vulnerable, because it is reflected in the dependence on imports of foreign defense equipment to meet the needs for the procurement of facilities and infrastructure for the national military defense equipment. Therefore, Indonesia seeks to be able to overcome the problem of dependence on defense equipment, which is reflected in defense cooperation with Turkey. This collaboration is carried out for the joint production of military defense equipment, especially the manufacture of Kaplan Medium Tanks in order to build the independence of the defense industry and modernize the national defense equipment so that it can improve Indonesia's position and bargaining power in Southeast Asia.